Ecological Approach to the Second Language (L2) Teaching and Nepali English Teachers - Rai, Vishnu S. (Studies in ELT and Applied Linguistics, 2021)
Ecological approach to L2 teaching is based on the concept of language ecology. In this ever changing world nothing is static. After so many approaches, methods, views, and ideas, ecological approach has made its appearance on the ELT stage. The approach is new to many Nepali English teachers who equate it with teaching ecology through the English language. The present paper explores the origin of the approach, shows differences between ecological approach to L2 (English) from teaching ecology through English, presents situation of language ecology, and ELT in Nepal, and suggests what could be possibly the best ways to teach English in Nepal.